2020
DOI: 10.1186/s12955-020-1269-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with quality of life of adult patients with acute leukemia and their family caregivers in China: a cross-sectional study

Abstract: Background: Acute leukemia (AL) not only impairs the quality of life (QOL) of patients, but also affects that of their family caregivers (FCs). Studies on QOL of AL patients and their FCs are limited. This study aimed to evaluate the QOL of AL patients and their FCs, and to explore the factors associated with QOL of patients and of FCs. Methods: A multicenter cross-sectional study was conducted. The QOL of 196 patient-FC dyads was assessed. The Functional Assessment of Cancer Therapy-Leukemia (FACT-Leu) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
2
19
0
6
Order By: Relevance
“…Today, more attention is being paid to meeting the needs of patients suffering from other types of cancer, such as prostate and breast cancer, in order to improve cancer patients' QoL [18,19]. Previous studies have shown that patients with AL have a low QoL [20].…”
Section: Introductionmentioning
confidence: 99%
“…Today, more attention is being paid to meeting the needs of patients suffering from other types of cancer, such as prostate and breast cancer, in order to improve cancer patients' QoL [18,19]. Previous studies have shown that patients with AL have a low QoL [20].…”
Section: Introductionmentioning
confidence: 99%
“…Lingkungan mempunyai dampak yang cukup signifikan terhadap kualitas hidup pasien. Dimana lingkungan tersebut merupakan salah satu sarana untuk beraktivitas pasien, sehingga sangat memperngaruhi kondisi fisik dan psikologis pasien (Wang et al, 2020). Perubahan peran sosial yang terjadi pada saat pasien sakit akan membawa dampak tersendiri bagi pasien tersebut, sehingga bisa mengakibatkan depresi dan ansietas.…”
Section: Lingkunganunclassified
“…Extensive research has been conducted into identifying the health-care needs of family caregivers and the effects of the cancer diagnosis on patients' families [8,9]; however, few experimental studies have been undertaken according to family caregivers' attitude and need, speci cally and functionally to address the psychological distress experienced by the family caregivers of leukemia patients [10]. Regarded that whilst SEER data indicate very limited increase with time from 1975 to 2017 for all types of leukemias, and estimated new cases in 2020 in the USA were 60,530 all types with a moderate increase in ALL and AML from 1992 to 2017 [11], the annual new incidence rate for leukemia has been estimated to range from 0.1 to 1.5 per 100,000 individuals and the prevalence of this disease has been estimated to be 24 per 100,000 people over the world [12].…”
Section: Introductionmentioning
confidence: 99%